Promotion of Intrinsic Motivation of New Generation Learners for Learning Physics by Digital Physics Labs - Peciuliauskiene, Palmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the role of digital Physics experiments in the promotion of intrinsic motivation of secondary school age learners for learning Physics. The methodological basis of research is inquiry-based learning. The article focuses on the second level of inquiry-based learning referred to as structured inquiry. The study is based on the sociological approach, with the emphasis on the new generation (Generation Z) and their exclusive relationship to technology. The research problem is formulated as a question: how does digital Physics laboratory promote intrinsic motivation of the new generation learners?Learners’ intrinsic motivation is analysed on the basis of Self-Determination Theory. Despite this theory, motivation is based on three basic needs: a need for autonomy, a need for competency and a need for social relatedness. The article examines how digital Physics labs provide basic psychological needs for autonomy, competency and social relatedness of eighth-form learners.